Acute kidney injury after in-hospital cardiac arrest. (March 2021) - Mah, Kenneth E.; Alten, Jeffrey A.; Cornell, Timothy T.; Selewski, David T.; Askenazi, David; Fitzgerald, Julie C.; Topjian, Alexis; Page, Kent; Holubkov, Richard; Slomine, Beth S.; Christensen, James R.; Dean, J. Michael; et al.
Abstract: Aim: Determine 1) frequency and risk factors for acute kidney injury (AKI) after in-hospital cardiac arrest (IHCA) in the Therapeutic Hypothermia after Pediatric Cardiac Arrest In-Hospital (THAPCA-IH) trial and associated outcomes; 2) impact of temperature management on post-IHCA AKI. Methods: Secondary analysis of THAPCA-IH; a randomized controlled multi-national trial at 37 children's hospitals. Eligibility: Serum creatinine (Cr) within 24 h of randomization. Outcomes: Prevalence of severe AKI defined by Stage 2 or 3 Kidney Disease Improving Global Outcomes Cr criteria. 12-month survival with favorable neurobehavioral outcome. Analyses stratified by entire cohort and cardiac subgroup. Risk factors and outcomes compared among cohorts with and without severe AKI. Results: Subject randomization: 159 to hypothermia, 154 to normothermia. Overall, 80% (249) developed AKI (any stage), and 66% (207) developed severe AKI. Cardiac patients (204, 65%) were more likely to develop severe AKI (72% vs 56%, p = 0.006). Preexisting cardiac or renal conditions, baseline lactate, vasoactive support, and systolic blood pressure were associated with severe AKI. Comparing hypothermia versus normothermia, there were no differences in severe AKI rate (63% vs 70%, p = 0.23), peak Cr, time to peak Cr, or freedom from mortality or severe AKI (p = 0.14). Severe AKI was associated with decreased hospital survival (48% vs 65%, p = 0.006) and decreased 12-month survival with favorable neurobehavioral outcome (30% vs 53%, p < 0.001). Conclusion: Severe post-IHCA AKI occurred frequently especially in those with preexisting cardiac or renal conditions and peri-arrest hemodynamic instability. Severe AKI was associated with decreased survival with favorable neurobehavioral outcome. Hypothermia did not decrease incidence of severe AKI post-IHCA.